Economic and Sustainability: The Moderating Role of Government Quality on Environmental Deterioration in E7 Countries - Najma Taralia Farah; Anton Bawono; Citra Ayudiati (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
This study aims to analyze the balance between economic growth and environmental sustainability by considering the moderating role of government quality in Emerging Seven (E7) countries using a quantitative methodology utilizing panel data from 2015 to 2024, along with the Generalized Method of Moments (GMM) and Moderated Regression Analysis (MRA) to examine the causal relationships between variables. The findings indicate that economic growth and population metrics have a positive impact on carbon emission escalation, while trade openness does not appear to have a statistically significant effect. In contrast, Foreign Direct Investment (FDI) initially presents a negative effect on carbon emissions, which shifts to a positive correlation in the context of declining government quality. This demonstrates that good governance can strengthen efforts to control carbon emissions and promote sustainable development. Thus, institutional capacity building and robust environmental policies are key to balancing economic growth and environmental preservation in E7 countries.